Ultrafine particles induce ferroptosis-like stress features in human dopaminergic LUHMES cells via the p53/xCT/GSH/cGPx4 axis - Emma Theerens; Aurélie Jonneaux; Lydia Nikasinovic; Ophélie Simonin; Jean-Christophe Devedjian; Esperanza Perdrix; Véronique Riffault; Laurent Y. Alleman; Anne-Sophie Rolland; Guillaume Garçon; David Devos (Toxicology in Vitro, 2026)

Publisher Correction: Livestock husbandry in Islamic Cártama, Málaga, Spain: The micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2026)

Multi-organ toxicity of ultrafine particles derived from air pollution: a sub-chronic exposure study in mice - Emeline Barbier; Jessica Carpentier; Pierre Gosset; Laurent Y. Alleman; Esperanza Perdrix; Kelly Timmerman; Anne-Sophie Rolland; David Devos; Guillaume Garçon (Environmental Science and Pollution Research, 2025)

Livestock husbandry in Islamic Cártama, Málaga, Spain: the micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2025)
Multidisciplinary micro- and bioarchaeological analyses of late medieval deposits from suburban Cártama, Málaga, Spain, have, for the first time, confidently identified open air fumier deposits, which are supported by preliminary analysis of the faunal assemblage. This demonstrates that Andalusi livestock husbandry practices included periodically burning animal dung within corrals and pens, which is a long-standing practice in the Mediterranean region also observed in prehistoric transhumance. These techniques have commonly been applied to prehistoric fumier or pastoral sites and now demonstrate the importance of expanding micro- and bioarchaeological work to fumier sequences from other periods. This research from Cártama offers a window into the so-called medieval “Green Revolution” associated with Arab migrations and highlights the necessity of identifying in situ penning deposits on archaeological sites and of applying high resolution analyses to examine them. The analyses reveal data on animal feeds, including pearl millet ( Pennisetum glaucum ) and sorghum ( Sorghum bicolor ) which are rare in the Iberian Peninsula at this time, the use of plant resources in livestock husbandry, and the preparation of fertiliser, which are central to understanding farming practices in Al-Andalus.

S01-04 Advancing mixture risk assessment from a regulatory point of view - B. Dujardin; C. Cascio; A. Cafaro; Y. Devos; J.-L.C.M. Dorne; J. Fabrega; G. Giner Santonja; C. Heppner; S. Levorato; L. Mohimont; A. Papanikolaou; E. Solazzo (Toxicology Letters, 2024)

Fecal biomarkers in Italian anthropogenic soil horizons and deposits from Middle Ages and bronze age - M. Bortolini; C. Nicosia; E. Argiriadis; G. Pojana; Y. Devos; D. Battistel (Quaternary Science Reviews, 2024)

Impact of combination therapy with aminoglycosides on the outcome of ICU-acquired bacteraemias - P.-Y. Delannoy; N. Boussekey; P. Devos; S. Alfandari; C. Turbelin; A. Chiche; A. Meybeck; H. Georges; O. Leroy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Collaboration between the EFSA GMO Panel and national EU competent authorities for the environmental risk assessment of GM crop cultivation applications - Karine Lheureux; S. Mestdagh; Y. Devos (Journal of Consumer Protection and Food Safety, 2009)